Genetic parameters estimate for plant characters of a particular carrot population in two different agroecologic cultivation systems (Bioscience Journal, 2020)
Carrots are among the most planted vegetables in Brazil, which represents importance in the national market. This crop can be grown in conventional and agroecological systems, and studies to improve productivity, disease resistance and root quality in agroecological cropping systems are important. The aim of the present work was to estimate genetic parameters that provide a breeding strategy in the search for the development of new varieties of carrot adapted to the conditions of Distrito Federal’s agroecology cultivation. Considering data from tests performed in areas of agroecology cultivation (Natural Agriculture-NA and Organic Agriculture-OA), the following characteristics were evaluated: incidence of leaf blight-LB, incidence of root cracking-CRACK, root length-COMP, format of root tip-TP, format of root shoulder-TO, measure of the color of the a* xylem parameter-a*X, measure of the color of the a* phloem parameter-a*F. Traits were evaluated in 100 half-sib progenies derived from Brasília cultivar, using a completely randomized block design. For the characters COMP, a*X, a*F, TP and TO, the treatment X environment interaction was significant according to the results from test F. The values of the individual variance analyses presented significant effect for the following characteristics: COMP, a*X, TP, TO, LB for NA system, and COMP, a*X, a*F, TP for OA system. In NA system, the values of heritability estimates-ha² for the plant characters fluctuated from 65.66 to 25.52% and, in the OA system, the ha² of the characters a*X, was 81.13%. Estimates of genetic gain per cycle for the characters a*X and a*F were lower in NA system than the estimates observed in OA system.